Usefulness of bronchoalveolar lavage in the management of patients presenting with lung infiltrates and suspect COVID-19-associated pneumonia: A case report - Gualano, Gina (Int J Infect Dis, 2020)
OBJECTIVE: To report a clinical case of a patient with a compatible HRCT scan and two negative SARS-CoV-2 RNA upper respiratory tract specimens but with a confirmed viral infection by BAL (19 days after symptom onset). METHODS: Revision of a patient’s clinical charts with COVID-19 admitted at INMI L. Spallanzani Hospital RESULTS: Two oropharyngeal swab tests of SARS-CoV-2 by qualitative real-time reverse-transcriptase-polymerase-chain-reaction (RT-PCR) assay were performed at admission (17 days from symptoms onset) and a day apart and were found negative. BAL fluid collected 19 days after symptoms onset was positive for SARS-CoV-2. CONCLUSION: This case highlights importance of clinical suspicion of SARS-CoV-2 infection in diagnosis and infectivity assessment. We suggest collection of BAL fluid when consecutive nasopharyngeal swabs are negative, to confirm or exclude the diagnosis of COVID-19-associated pneumonia. Healthcare workers should perform aerosol-generating procedures in an adequately ventilated room and should wear adequate PPE.